Rząd generała Władysława Sikorskiego (16 grudnia 1922 – 26 maja 1923). Geneza, skład i działalność - Goclon, Jacek (Przegląd Nauk Historycznych, 2013)
The Government of general Sikorski was establish under very dramatical circumstances: after the murder of President Gabriel Narutowicz (Mr Ludwik Darowski has rejected the mission of construction of new government) the new Premier Minister was general Władysław Sikorski. In practice out of the Parliament government, what was created by the General, in short time lost the support of the Polish Parliament. It was active only six months and in consequence was unable to achieve any target described in the Premiere expose; first of all to rep air the state treasure, or the Policy for the natives minorities (in reality the cabinet did only the analyze concern the actual natives minorities status). In foreign activity it was not achieved a close connection with United Kingdom (even the cooperation with France was not so close as was expected by Polish government), or the relationships with Soviet Union and Czechoslovak Republic was not satisfied. The solid success of the government was (thanks full mainly by ministry of the treasure, Władysław Grabski) the action against the inflation of Polish currency. In the legislation domain the main achievement was the law to establish the State Tribunal. Also was started some acts and works over the changes in state administration and it was improved the works over the construction of new sea port in Gdynia.